Blur and Quality Metrics in Digital Images (Eurasian Journal of Research, Development and Innovation, 2024)
Modern digital cameras have provided a great service to users of different groups and ages as they have facilitated the process of obtaining images. However, the user still needs to improve some images that are marred by lack of clarity when taking the image due to the lack of appropriate lighting such as cloudy weather, bright light, or dark locations. Or taking the photo from a long distance, which leads to blurring of image details and blurring of colors. Therefore, through this research, Contrast Enhancement algorithms were used in images because of their significant impact in modifying the lighting in dark images, clarifying their edges, clarifying their features, and improving image quality. The issue of poor contrast in images is one of the most common problems facing users or researchers when working on scientific images or in the case of general use of images